1995
DOI: 10.1128/mcb.15.10.5246
|View full text |Cite
|
Sign up to set email alerts
|

Pheromone Signalling in Saccharomyces cerevisiae Requires the Small GTP-Binding Protein Cdc42p and Its Activator CDC24

Abstract: Pheromone signalling in Saccharomyces cerevisiae is mediated by the STE4-STE18 G-protein ␤␥ subunits. A possible target for the subunits is Ste20p, whose structural homolog, the serine/threonine kinase PAK, is activated by GTP-binding p21s Cdc42 and Rac1. The putative Cdc42p-binding domain of Ste20p, expressed as a fusion protein, binds human and yeast GTP-binding Cdc42p. Cdc42p is required for ␣-factor-induced activation of FUS1. cdc24 ts strains defective for Cdc42p GDP/GTP exchange show no pheromone inducti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
184
2

Year Published

1997
1997
2004
2004

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 190 publications
(193 citation statements)
references
References 75 publications
(63 reference statements)
7
184
2
Order By: Relevance
“…Inhibition of estrogen receptor activation by N17Cdc42Hs, coupled with the presence of a DH (GEF) region and a receptor-binding region, suggests that Brx may function as a molecular bridge between transmembrane signaling pathways and nuclear receptor signaling (see below). In keeping with this postulate, Cdc42Hs, has been implicated in seven transmembrane growth factor receptor signaling in both NIH3T3 cells (Nobes and Hall, 1995) and yeast (Zhao et al, 1995). We note that binding of Brx to ER may not precisely correlate with the ability of Brx to augment estrogendependent reporter activity, since transfection of a Brx expression mutant similar to the DC1 fragment that failed to bind ER (Figure 4d) did cause a slight increase in estrogen-dependent reporter activity (not shown).…”
Section: Discussionsupporting
confidence: 55%
“…Inhibition of estrogen receptor activation by N17Cdc42Hs, coupled with the presence of a DH (GEF) region and a receptor-binding region, suggests that Brx may function as a molecular bridge between transmembrane signaling pathways and nuclear receptor signaling (see below). In keeping with this postulate, Cdc42Hs, has been implicated in seven transmembrane growth factor receptor signaling in both NIH3T3 cells (Nobes and Hall, 1995) and yeast (Zhao et al, 1995). We note that binding of Brx to ER may not precisely correlate with the ability of Brx to augment estrogendependent reporter activity, since transfection of a Brx expression mutant similar to the DC1 fragment that failed to bind ER (Figure 4d) did cause a slight increase in estrogen-dependent reporter activity (not shown).…”
Section: Discussionsupporting
confidence: 55%
“…Database searches revealed that the cloned cDNA encodes a protein kinase highly related to LOK, a Ste20-related protein kinase preferentially expressed in lymphocytes (Kuramochi et al, 1997). Analysis of the kinase domain shows that SLK is also related to MST1/2 (Creasy and Cherno , 1995; Katoh et al, 1995;Schinkmann and Blenis, 1997) and more distantly related to Ste20, a yeast kinase involved in the pheromone response pathway (Zhao et al, 1995). Furthermore, SLK showed 70% identity to M-NAP and 63 and 71% identity to AT1-46 in two distinct carboxy terminal domains.…”
Section: Discussionmentioning
confidence: 99%
“…In yeast, the Ste20 serine/threonine protein kinase regulates a mitogen-activated protein kinase pathway consisting in Ste11 (MEK kinase), Ste7 (MEK) and Fus3/Kss1 (MAPK) protein kinases involved in the control of mating response (Zhao et al, 1995). Alpha factor binding to its G-protein coupled receptor results in the downstream activation of Ste20 by the bg complex released from the heterotrimeric G protein.…”
Section: Introductionmentioning
confidence: 99%
“…Free bg dimers then activate a serine-threonine kinase, Ste20, stimulating the activity of a linear cascade of kinases including sequentially Ste11 and Ste7, which phosphorylate and activate the yeast MAPK homolog Fus3 and Kss1. Extensive search for molecules linking yeast bg complexes to Ste20 has led to the recent discovery that Cdc42 participates in Ste20 activation (Simon et al, 1995) and that Ste4 might directly bind and activate Cdc24, a nucleotide exchange factor for Cdc42 (Zhao et al, 1995). Thus, in yeast, the G protein b subunit can initiate activity of a MAPK cascade by binding an exchange factor for the Cdc42 GTPase, and then this GTP-binding protein physically interacts with the most upstream kinase, Ste20, causing its activation (Herskowitz, 1995).…”
Section: Novel Signaling Pathways Communicate Gpcrs To the Nucleusmentioning
confidence: 99%